PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TURNAMENT (TGT) BERBANTUAN MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 2 SRIKATON MUSI RAWAS - Venti Yurika Indriayani; Akmal Rijal; Dedy Firduansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of implementing the Teams Games Tournament (TGT) learning model assisted by the Snakes and Ladders media on the IPAS learning outcomes of fourth-grade students at SD Negeri 2 Srikaton Musi Rawas. This study employed a pre-experimental method using a One Group Pre-test Post-test Design. The sample consisted of 23 students selected through a saturated sampling technique. Data were collected using learning achievement tests and analyzed using the normality test and Z-test. The results showed that the mean pre-test score increased from 54.73 to 85.13 in the post-test. Learning mastery also improved from 17% to 92%. The normality test indicated that the data were normally distributed, while the hypothesis test showed that Zcount = 4.96 was greater than Ztable = 1.64, indicating that Ha was accepted and H₀ was rejected. Therefore, it can be concluded that the implementation of the Teams Games Tournament (TGT) learning model assisted by the Snakes and Ladders media had a significant effect on improving the IPAS learning outcomes of fourth-grade students at SD Negeri 2 Srikaton Musi Rawas.